Effectiveness of a Primary Care Telerehabilitation Program for Post-COVID-19 Patients: A Feasibility Study - Dalbosco Salas, Marcelo.; Torres Castro, Rodrigo.; Rojas Leyton, Andrés.; Morales Zapata, Franco.; Henríquez Salazar, Elisabeth.; Espinoza Bastías, Gabriel.; Beltrán Díaz, María Elizabeth.; Tapia Allers, Kris.; Mornhinweg Fonseca, Daniela.; Vilaró, Jordi (MDPI, 2021)
In many health systems, it is difficult to carry out traditional rehabilitation programs as the systems are stressed. We evaluate the effectiveness of a telerehabilitation program conducted in primary care in post-COVID-19 patients. An observational, prospective study was conducted in seven primary care centers in Chile. We included adult patients (>18 years) with a previous SARS-CoV-2 infection. The telerehabilitation program consisted of 24 sessions of supervised home-based exercise training. The efficacy was measured by the 1-min sit-to-stand test (1-min STST), the 36-Item Short Form Health Survey (SF-36), fatigue, and dyspnea symptoms before and after intervention. We included 115 patients (55.4% female) with a mean age of 55.6 ± 12.7 years. Fifty-seven patients (50%) had antecedents of hospitalization, and 35 (30.4%) were admitted to the ICU. The 1-min STST was improved after the intervention from 20.5 ± 10.2 (53.1 ± 25.0%predicted) to 29.4 ± 11.9 (78.2 ± 28.0%predicted) repetitions (p < 0.001). The SF-36 global score improved significantly from 39.6 ± 17.6 to 58.9 ± 20.5. Fatigue and dyspnea improved significantly after the intervention. Although limited by the absence of a control group, this report showed that a telerehabilitation program applied in primary health care is feasible and was effective in improving physical capacity, quality of life and symptoms in adult survivors of COVID-19.
Keywords: COVID-19; Dyspnea; Fatigue; Physical capacity; Quality of life; Telerehabilitation